A Female Perspective on Sami Bear Ceremonies - Westman Kuhmunen, Anna (Journal of Northern Studies, 2016)
Researchers have often seen Sami bear ceremonies as exclusive male activities since the hunting was performed by men. This asymmetrical outlook on men’s and women’s participation in rituals is partly due to the old source material, which generally has a male point of departure. This view has also been reinforced by later researchers. By introducing Anna Tomasdotter and her account of the Sami bear ritual, a source not frequently used, the author of the article brings to the fore a female perspective on the ceremony. The complementary gender roles in Sami religion are thus put in focus.